Perceived Challenges of Start Up of Small and Medium Scale Enterprises Among Business Education Graduates in Federal Colleges of Education in North-East, Nigeria - Mohammed, H., Amin; Adamu, I., Alhaji (Kashere Journal of Education, 2021)
The aim of the study was to determine the Perceived Challenges of Start-up of Small and Medium scale Enterprises (SMEs) among Business Education graduates in Federal Colleges of Education in North-East Nigeria. The study was guided by the following research questions: To what extent does Startup capital constitute a challenge in setting up of Small and medium scale enterprises (SMEs) among business education students in Federal Colleges of Education in North-east, Nigeria? To what extent does Inadequate Entrepreneurial Skills constitute a challenge in startup of small and medium enterprises (SMEs) among Business Education graduates in Federal Colleges of Education in North east Nigeria? The design of the study was descriptive survey. The area of the study was North-east, Nigeria; population of the study comprises 639 final year Business Education graduates of Federal Colleges of Education who are trained in Entrepreneurship Education as a course, stratified proportionate random sampling technique was used. The instrument for data collection in the study was a structured questionnaire developed by the researcher. The instrument was validated by two experts from the Department of Vocational and Technology Education, Faculty of Technology Education, Abubakar Tafawa Balewa University, Bauchi. Reliability coefficient of 0.81 was obtained which indicates that the instrument was highly reliable. The researchers used a research assistant for administering of the questionnaire. The data collected was analysed using mean and standard deviation using Statistical Package for Social Science (SPSS) software, version 23. The result of the study revealed that graduates of Federal colleges of education were faced with the challenges of start-up capital in setting up of Small and Medium scale Enterprises (SMEs), also the study revealed that there are inadequate Entrepreneurial skills training in setting up of SMEs among Business Education graduates. Based on the findings it was recommended that Government should increase support given to federal colleges of education in order to boost training of entrepreneurial skills and to provide financial support to students of Business Education to start-up SMEs after graduation.